Neutrophil Recruitment and Participation in Severe Diseases Caused by Flavivirus Infection - Marina Alves Fontoura; Rebeca Fróes Rocha; Rafael Elias Marques (Life, 2021)
Neutrophils are first-line responders to infections and are recruited to target tissues through the action of chemoattractant molecules, such as chemokines. Neutrophils are crucial for the control of bacterial and fungal infections, but their role in the context of viral infections has been understudied. Flaviviruses are important human viral pathogens transmitted by arthropods. Infection with a flavivirus may result in a variety of complex disease manifestations, including hemorrhagic fever, encephalitis or congenital malformations. Our understanding of flaviviral diseases is incomplete, and so is the role of neutrophils in such diseases. Here we present a comprehensive overview on the participation of neutrophils in severe disease forms evolving from flavivirus infection, focusing on the role of chemokines and their receptors as main drivers of neutrophil function. Neutrophil activation during viral infection was shown to interfere in viral replication through effector functions, but the resulting inflammation is significant and may be detrimental to the host. For congenital infections in humans, neutrophil recruitment mediated by CXCL8 would be catastrophic. Evidence suggests that control of neutrophil recruitment to flavivirus-infected tissues may reduce immunopathology in experimental models and patients, with minimal loss to viral clearance. Further investigation on the roles of neutrophils in flaviviral infections may reveal unappreciated functions of this leukocyte population while increasing our understanding of flaviviral disease pathogenesis in its multiple forms.